2021
DOI: 10.3390/vaccines9080852
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Immunogenicity of a Candidate DNA Vaccine Expressing SARS-CoV-2 Spike Subunit 1

Abstract: The urgent need for effective, safe and equitably accessible vaccines to tackle the ongoing spread of COVID-19 led researchers to generate vaccine candidates targeting varieties of immunogens of SARS-CoV-2. Because of its crucial role in mediating binding and entry to host cell and its proven safety profile, the subunit 1 (S1) of the spike protein represents an attractive immunogen for vaccine development. Here, we developed and assessed the immunogenicity of a DNA vaccine encoding the SARS-CoV-2 S1. Following… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Most reported COVID-19 DNA vaccines and candidates encode spike, S1, or RBD protein. [31][32][33] In the context of the continuous circulation of SARS-CoV-2, this study provided a new DNA vaccine candidate and a heterologous prime-boost approach with potent immunogenicity to expand the vaccine development pipeline. In this sense, this piece of work showed the privilege of DNA prime for the cellular response, better than the current protein prime.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported COVID-19 DNA vaccines and candidates encode spike, S1, or RBD protein. [31][32][33] In the context of the continuous circulation of SARS-CoV-2, this study provided a new DNA vaccine candidate and a heterologous prime-boost approach with potent immunogenicity to expand the vaccine development pipeline. In this sense, this piece of work showed the privilege of DNA prime for the cellular response, better than the current protein prime.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the most important requirements for the anti-COVID-19 vaccines that are safeness, protectiveness, accessibility, and inexpensiveness can be achieved via DNA vaccines [ 16 ]. Studies have already demonstrated the positive outcome of the DNA vaccine of SARS-CoV-2 spike protein [ 47 , 48 ]. Interestingly, there are already several DNA vaccines approved for veterinary use including a vaccine against highly pathogenic H5N1 Influenza A virus in chicken [ 49 ], the vaccine against West Nile virus in horses, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The authors commented that NFIS delivery enhanced the immune responses in this study and that combining NFIS with EP delivery should also be investigated to determine if the combination of delivery methods would further enhance the immune response [ 55 ]. The group also tested their pVAX-S1 DNA vaccine in mice given IM with the modified Tropis ( Table 2 ), showing similar results [ 87 ].…”
Section: Nfis Delivery Of Dna Vaccines For Pandemic Virusesmentioning
confidence: 98%
“…NFIS use has also shown less intra-group variability in immune responses [ 55 , 79 ]. Both humoral and cellular immunity can be effectively induced with NFIS delivery [ 17 , 29 , 30 , 52 , 55 , 81 , 83 , 87 , 94 , 98 ], in addition to producing unique types of immune responses such as a Th1-biased response with COVID-19 vaccines [ 55 , 86 , 87 ]. Additionally, studies discussed here show that pre-clinical results can translate to clinical trial results, with ZyCoV-D as an example, where results observed in NHP were repeated in clinical trials [ 29 , 83 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%